LVRT Control Strategy for Three-Phase Grid Connected PV System - Poudel, Samip; Ghimire, Pallavi; Pandey, Pratyus; Nepal, Sushma; Tamrakar, Indraman; Bhandari, Harish (KEC Journal of Science and Engineering, 2023)
With increasing interest in Photo Voltaic systems in the international market, proper protection system implementation is required in the grid-connected PV System. Traditionally it is seen that a grid-connected PV system is discontinued during a transient fault period to protect the inverter from power imbalance between the PV side and the grid side. This paper presents a Low Voltage Ride Through control strategy for the system to continue supplying to the grid even during fault conditions. The low Voltage Ride Through strategy is achieved by adding a discharge circuit to the DC-link of the inverter and modifying the id and IQ current reference to the inverter when grid voltage sag occurs. A 50 KW two-stage photovoltaic system model is designed in MATLAB platform with a PV array, Boost Converter, 3-phase DC/AC inverter, filter, and the grid. Maximum power point tracking (MPPT) control scheme is adopted in Boost Converter to track maximum power in our system, and for the control, the inverter hysteresis band control strategy is employed. A separate discharging circuit was adopted on the dc side for LVRT operation. Simulation results using MATLAB verifies the validity of the proposed control strategies under symmetrical voltage sag conditions.